(untitled) (International relations and international law Journal, 2025)
The scientific article examines the illegitimate practice of applying the US sanctions policy towards the People’s Republic of China and retaliatory measures to Washington’s actions. Against the background of the deepening confrontation in US-China relations and the introduction of illegal unilateral restrictions by the US, China has begun to firmly improve legal regulation aimed at countering restrictive measures. Currently, the sanctions policy is rapidly gaining momentum, leading to severe humanitarian consequences, aggravating the negative manifestations of both bilateral and multilateral interstate dialogue. In the modern world, sanctions have become a mechanism of foreign policy in relation to those states that independently conduct foreign policy, adhere to their own path of development. In modern conditions, the problem of applying sanctions policy by one state (group of states) in relation to another state, the same equal subject of international relations, is relevant. In the context of the media discourse of the official news agencies of the government of the People’s Republic of China, the scientific work reveals the mechanism of forced use of illegal measures against geopolitical competitors. Aspects of the inefficiency of the existing system of multilateral regulation of international relations, which have been widely used in recent decades, are presented. The article structures the determinants of external threats, an attempt at overt interference in the internal affairs of a sovereign state, and the dynamic nature of the sanctions policy and its relevance in the context of geopolitical and geo-economic transformations emphasizes the importance of studying this topic. Keywords: sanctions policy, international relations, foreign policy of the state, People’s Republic of China, United States of America collective West.